Activation of Male Liver Chromatin Accessibility and STAT5-Dependent Gene Transcription by Plasma Growth Hormone Pulses - Connerney, Jeannette (Endocrinology, 2017)
Sex differences in pituitary growth hormone (GH) secretion (pulsatile in males vs near continuous/persistent in females) impart sex-dependent expression to hundreds of genes in adult mouse liver. Signal transducer and activator of transcription (STAT) 5, a GH-activated transcription factor that is essential for liver sexual dimorphism, is dynamically activated in direct response to each male plasma GH pulse. However, the impact of GH-induced STAT5 pulses on liver chromatin accessibility and downstream transcriptional events is unknown. In this study, we investigated the impact of a single pulse of GH given to hypophysectomized mice on local liver chromatin accessibility (DNase hypersensitive site analysis), transcription rates (heterogeneous nuclear RNA analysis), and gene expression (quantitative polymerase chain reaction and RNA sequencing) determined 30, 90, or 240 minutes later. The STAT5-dependent but sex-independent early GH response genes Igf1 and Cish showed rapid, GH pulse–induced increases in chromatin accessibility and gene transcription, reversing the effects of hypophysectomy. Rapid increases in liver chromatin accessibility and transcriptional activity were also induced in hypophysectomized male mice for some (Ces2b, Ugt2b38) but not for other liver STAT5-dependent male-biased genes (Cyp7b1). Moreover, in pituitary-intact male mice, Igf1, Cish, Ces2b, and Ugt2b38 all showed remarkable cycles of chromatin opening and closing, as well as associated cycles of induced gene transcription, which closely followed each endogenous pulse of liver STAT5 activity. Thus, the endogenous rhythms of male plasma GH pulsation dynamically open and then close liver chromatin at discrete, localized regulatory sites in temporal association with transcriptional activation of Igf1, Cish, and a subset of STAT5-dependent male-biased genes.